Infant Massage and Its Effects on Maternal-Infant Bonding, Sleep Quality, and Jaundice Reduction: A Meta-Analysis - Setiyarini, Dwi Wahyu; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2025)
Background: Baby massage is defined as the oldest tactile therapy practiced for hundreds of years and can affect a baby’s development. Baby massage is essential for the emotional bonding process of mother and child. In terms of sleep quality, massaged babies will have better sleep quality. Baby massage is also effective in lowering blood bilirubin levels in babies with jaundice. This study aims to estimate the effect size based on the results of previous similar primary studies. Subjects and Method: A meta-analysis was conducted on a number of primary studies with a Randomized Controlled Trial (RCT) design. The research questions were conducted in the PICO format. Population: infants aged 0-3 years, Intervention: infant massage, Comparison: no infant massage, Outcome: emotional relationship between mother and child, sleep quality, blood bilirubin level. The article search was conducted using a database of journals including PubMed, Sains direct, Google Scholar, Publish or Perish and SpringerLink Articles for the 2012-2023 period with the keywords "baby massage" or "infant massage" and "sleep quality" or "baby sleep quality" and "attachment" or " bonding" and "jaundice" or "hyperbilirubinemia" and "randomized control trial". Data analysis in this study was carried out using the Review Manager application (RevMan 5.4). Results: This meta-analysis was conducted on 20 primary studies of Randomized Controlled Trials (RCTs), originating from Indonesia, Taiwan, Iran, Turkey, and Iceland. The total sample size is 2,043 children. The results of the meta-analysis discovered that infant massage lowered bilirubin levels (SMD = -2.07; 95% CI = -2.71 to -1.43, p<0.001). Infant massage improved sleep quality (SMD = 0.90; 95% CI = 0.44 to 1.36, p<0.001) and maternal and child emotional bonding (SMD = 9.92; 95% CI= 7.72 to 12.12, p<0.001). Conclusion: Baby massage lowers bilirubin levels. Baby massage improves the quality of sleep and the emotional relationship of mother and child.